Analisis Implementasi Keadilan Kompensasi di PT. Jasa Raharja (Persero) Kantor Cabang Jawa Tengah - Priyanti, Oktavina Herdiani; Yuniawan, Ahyar (Diponegoro Journal of Management, 2015)
Increasingly complex and intense competition in the service industries has forced top managers to seek the most appropriate strategies to win the competition. One of the strategies to achieve success in the service industry,is the applicationof the equity compensation plays an important role in the empowerment of human resources, because in the service industry, human resources potential spearheading the company's success. So far, research on equity compensation is still minimal, for that is the need for research that addresses fairness in compensation as the main topic.Research "Analysis of the Implementation of Justice Compensation in PT. Jasa Raharja (Persero) Branch in Central Java" make PT. Jasa Raharja (Persero) Branch in Central Java as an object of study the implementation of justice compensation. PT. Jasa Raharja (Persero) is used as a research object because it already has offices spread throughout Indonesia which is an SOEs but shaped Persero who have rights and obligations as the other than as a government company also has rights and obligations as the company in general so, it can be used as one example of the fairness compensation or view that is currently happening in Indonesia.The study aims to analyze and determine the extent to which the implementationÂ  ofequity compensation applied by the company and how the company justice. Research "Analysis of the Implementation of Justice Compensation in PT Jasa Raharja (Persero) Branch in Central Java" made against employees of PT Jasa Raharja (Persero) Branch Central Java using the case study method. The data used in this study is documentation of data company, literature data and interview data. Type of study is a qualitative research. The sampling is done by purposive is based on the criteria of field work, position level and years of service. Data analysis is done by using data reduction taking into account the validity of the data that has been obtained. Subjects in the study "Analysis of the Implementation of Justice Compensation in PT. Jasa Raharja (Persero) Branch in Central Java" is an employee of PT Jasa Raharja (Persero) Branch Central Java which is considered to with the criteria of field work,level position and the work period corresponden to research objectives.